LINEAR EQUATIONS OVER COMMUTATIVE RINGS AND DETERMINANTAL IDEALS - Elvina Herawaty (Proceedings of ICMSA, 2005)
This paper discusses about necessary and sufficient condition for linierequations over commuktive rings and relation to determinantal ideals.Keywords: system, vector, Crame's rule.